Bombil Fish (Bombay Duck) - Mumbai Archive Project Team (Jio Institute, 2024)
Bombil fish, also known as Bombay duck, is often dried in the sun as a traditional method of preservation. The dehydration process inhibits the growth of bacteria and moulds, extending the shelf life of the fish. The drying process removes excess moisture from the fish and concentrates its flavours, intensifying its taste and aroma.